Review of Different Routing Protocols in Mobile Ad-Hoc Networks - Gupta, Amit; Bisen, Dhananjay (International Journal of Computer Sciences and Engineering, 2015)
A Mobile ad-hoc network (MANET) is an infrastructure less network formed by collection of mobile nodes. Due to mobility of mobile nodes it supports Distributed routing protocols which are different from the conventional routing protocols like Distance-Vector Routing (what the routers tell each other) and Link-State Routing (how they use the information to form their routing tables). This paper discussed the issues and challenges of mobile ad hoc network responsible for the desire of different categories of routing protocols like proactive (table-driven), reactive (on-demand) and hybrid protocols with their comparisons based on different parameters.